The intention to use long-acting reversible contraception during the COVID-19 pandemic - Armini, Ni Ketut Alit; Yunita, Rahmi; Aria Auliaastiti (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the factors contributing to the intention to use long-acting reversible contraception among women of reproductive age during the coronavirus disease-2019 pandemic. Method: The cross-sectional study was conducted in Mlajah village, Bangkalan Madura, Indonesia, from May 25 to June 30, 2021, and comprised married women of reproductive age. Attitude, subjective norm, perceived behavioural control and intention to use long-acting reversible contraception were the elements explored using a questionnaire based on the Theory of Planned Behaviour. Data was analysed using Spearman’s Rho. Results: Of the 102 subjects, 46(45.1%) were aged 30-39 years, 51(50%) had college or university education, 43(42.2%) had 2 children and 59(57.8%) were using family planning methods. There was a significant relationship of intention to use long-acting reversible contraception with attitude (p=0.000; r=0.566), subjective norm (p=0.000; r=0.475), and perceived behavioural control (p=0.000; r= 0.691). Conclusion: The intention to use long-acting reversible contraception among married women of reproductive age was significantly associated with attitude, subjective norm and perceived behavioural control. Keywords: Behaviour control, Optimism, Contraception, Family planning, COVID-19, Women’s health.